Upstream stimulatory factor 2 (USF2) induced upregulation of triggering receptor expressed on myeloid cells 1 (TREM1) promotes endometritis by regulating toll-like receptor (TLR) 2/4-nuclear factor-kappaB (NF-κB) signaling pathway. Issue 2 (1st February 2022) - Zhang, Miao; Yin, Chengkun; Chen, Yan; Wang, Juan; Jiang, Jing
ABSTRACT: Triggering receptor expressed on myeloid cells 1 (TREM1) participates in the development of endometritis. This study aims at identifying the effects and interaction of TREM1 and upstream stimulatory factor 2 (USF2) in endometritis by using a model of lipopolysaccharide (LPS)-induced human endometrial epithelial cells (HEnEpCs). ELISA was performed to determine the levels of interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF-α) after LPS stimulation. TREM1 and USF2 expression was examined with RT-qPCR and Western blot. The JASPAR database was employed to predict the binding site between USF2 and TREM1, which was confirmed by luciferase reporter and chromatin immunoprecipitation assays. After TREM1 overexpression, IL-6, IL-1β, and TNF-α expression was detected by ELISA. Next, the binding of TREM1 to toll-like receptor (TLR) 2/4 was examined with co-immunoprecipitation. Then, proteins in TLR2/4-nuclear factor-kappaB (NF-κB) signaling in HEnEpCs under LPS condition were assessed by Western blot or immunofluorescence before and after TREM1 knockdown. Finally, TLR2 or TLR4 was silenced to explore whether intervene TLR2/4-NF-κB signaling pathway could rescue TREM1-overexpression-induced inflammation in LPS-induced HEnEpCs. Results revealed that upregulated TREM1 was observed in LPS-challenged HEnEpCs. Next, USF2 was found to have transcriptionally active TREM1 expression. Additionally, USF2 knockdown decreased the levels of IL-6, IL-1β, and TNF-α, whereas this effect was rescued after TREM1 overexpression. Besides, TREM1 could bind to TLR2/4 to regulate NF-κB signaling. Moreover, the intervention of TLR2/4-NF-κB signaling pathway rescued TREM1-overexpression-induced inflammation in LPS-stimulated HEnEpCs. Collectively, USF2 promotes endometritis by upregulating TREM1, thereby activating TLR2/4-NF-κB pathway.